The small projects and its role in developing the Muslim society: an applied study at Sultanate of Oman - Jokha Sulaiman Khalfan al-Hasni
The sector of small projects is the most capable sector for providing jobs, encouraging computation and flexible in making decisions. The problem statement of this research lays in the complicatedness that face these small projects and their owners which could be financial, marketing conditions, row materials availability, and dealing with laws and regulations. The study aims to show the importance and the role of the small projects (businesses) for the individuals. It also shows what their new ideas with regard to small businesses development and how it stimulates their capacity and skills. This study also aims to explore some small projects that serve individuals, and show the role of leaderships in putting the correct plans, which should help them build their economic lives. The Research methodology is descriptive and analytical approach. the study targeted the small community located in the governorate of Muscat; the capital of the Sultanate of Oman and other neighboring states. The study aimed at average 200 samples. The questionnaire was distributed to the owners of these projects, as these projects are registered officially in the Governmental States especially those concerned with businesses such as the Ministry of Manpower, Ministry of Trade and Industry, Ministry of National Economy. The finding of this study was reached because of many spread-funded institutions in the Sultanate of Oman, these bodies have contributed significantly to raising awareness of the importance of small projects to many of families in the targeted society. Plus it turned a large part of families' income into investments, which showed that the bulk of the amounts received from these institutions used in small outlets such as grocery, garments shops.